Analisis Pengaruh Posisi Peletakan Magnet Permanen Di Rotor Terhadap Kinerja Generator Sinkron Magnet Permanen - Harahap, Elco Maghfira Arfi; Rosma, Iswadi Hasyim; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Permanent Magnet Synchronous Generator (PMSG) has the same construction as conventional synchronous generators. The rotor in the synchronous generator requires DC current feeding to produce GGL while the PMSG rotor does not need DC current feeding because the magnetic field is generated from a permanent magnet. With this permanent magnet, it causes a cogging effect which inhibits the rotation of the stator. To reduce the cogging effect, it is necessary to change the position of the magnet in the motor. This scientific paper discusses the effect of the positioning of a Permenen magnet in the rotor on PMSG on the output of cogging voltage and torque from the modeling of PMSG magnets parallel and PMSG magnets of Skew. The PMSG design that was made refers to the specifications of the outer dimensions of 450 mm and a thickness of 150 mm with the Interior Permanent Magnet (IPM) type rotor using a combination of 24 slots 8 Poles with a rotating rotor at 750 rpm. To get the output values, PMSG must first be modeled into the software to be analyzed. When modeling the PMSG, it turns out that the mesh size of the generator constituent materials affects the level of accuracy at solving. So that the calculation results of the generated voltage, output power and torque will be more accurate. However, it takes a long time during the testing process. Based on the calculations and the results of the tests that have been carried out, it can be concluded that the position of the magnetic placement affects the generated output voltage. From the test results, a magnet with a skew position has a lower voltage than a normal / parallel magnet position. This is because the flux from the skew magnet that enters the stator teeth is imperfect plus there is a collision of flux / field direction from two different poles in one stator gear at the same time. As a result, the generated field becomes smaller. Then the second from the test results it is concluded that the positioning of the magnet affects the cogging torque. magnets that are placed in a skew position have a smaller cogging torque than parallel PMSG modeling. Keywords : Back EMF (Electromotive Force), Ke (Constant Efficiency), flux lingkage, cogging